Grassification and Fast-Evolving Fire Connectivity and Risk in the Sonoran Desert, United States - Wilder, Benjamin T.; Jarnevich, Catherine S.; Baldwin, Elizabeth; Black, Joseph S.; Franklin, Kim A.; Grissom, Perry; Hovanes, Katherine A.; Olsson, Aaryn; Malusa, Jim; Kibria, Abu S.M.G.; Li, Yue M.; Lien, Aaron M.; et al. (Frontiers in Ecology and Evolution, 2021)
Non-native grass invasions are connecting fire regimes, bridging the ecotone between deserts and forests that overlap with the wildland-urban interface (WUI). In southern and central Arizona winter annual and perennial non-native grasses are altering fuel types and facilitating fire spread, especially following wet El Niño events. A recent example of this was the 2020 Bighorn Fire in the Santa Catalina Mountains, which burned 486 km2, and prompted evacuations along a 40-km stretch of WUI on the outskirts of Tucson, AZ, a metropolitan area of >1M people. To better understand the changing nature of the WUI in semi-arid North America, we created a baseline map of the fire promoting non-native buffelgrass (Cenchrus ciliaris) in the Catalinas and evaluated the degree to which this species promoted the Bighorn Fire. We also quantified species responses to the fire, including losses of the iconic saguaro cactus (Carnegiea gigantea). To project forward, we simulated a coupled state-and-transition fire-spread model for ongoing buffelgrass invasion in the Catalinas. The Bighorn Fire was principally a forest fire driven by a long-history of fire suppression, fuels accumulation following a wetter than normal winter and spring, and two decades of hotter droughts, culminating in the hottest and second driest summer in the 125-yr Tucson weather record. Buffelgrass and other non-native species played a minor role in carrying the fire due to the patchiness of infestation at the upper edge of the Desertscrub biome. Burned areas in Desertscrub had high saguaro mortality rates as well as considerable resprouting by desert shrubs that may confer some post-fire resiliency. Our simulation models indicate a marked increase in both burned area and fire frequency if buffelgrass patches continue to expand and coalesce at the Desertscrub/Semi-desert Grassland interface. This case study captures a moment in time within a changing fire regime driven by invasive grasses that has the potential to create novel fire dynamics with increased risk to an expanding WUI. Sustained efforts to document and assess fast-evolving fire connectivity from the desert to the forest are needed throughout arid North America to understand and mitigate a fire prone future.